Climate change may drive cave spiders to extinction - Mammola, Stefano; Goodacre, S.L.; Isaia, Marco (Wiley, 2017)
Subterranean ecosystems present ideal opportunities to study mechanisms underlying responses to changes in climate because species within them are often adapted to a largely constant temperature. We have characterized the thermal conditions of caves in the Western Alps, and relate these hypogean climate data to the occurrence of Troglohyphantes troglobiontic spiders (Araneae, Linyphiidae). Our data indicate that present distributions reflect Pleistocence glaciation events and also point to specific responses as a consequence of changes in temperature. Constant temperatures recorded inside caves provide an approximation of the mean annual temperature outside, thus we extend the results to a regional scale. Ecological niche modeling is used to predict habitat suitability both in the Pleistocene and under future global warming scenarios. These analyses point toward a future decline in habitat suitability for subterranean spiders and the potential extinction of the most restricted endemic species.